Guest lecture and international community service at the Faculty of Vocational Universitas Sumatera Utara, Indonesia 6 – 7 September 2023 / Ahmad Fauzan Badiuzaman … [et al.] - Badiuzaman, Ahmad Fauzan; Othman, Mohd Syafiq; Azmi, Azila; Sulaiman, Suria; Ab Rashid, Putri Dahlia (UiTM Global @ Office of International Affairs, 2024)
Medan, Indonesia - The Faculty of Vocational, Universitas Sumatera Utara (USU) recently played host to a collaborative initiative aimed at advancing knowledge exchange and community development in the fields of gastronomy tourism, business marketing, and food innovation. From September 6 to 7 September 2023, esteemed guests from the Faculty of Hotel and Tourism Management at Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, participated in a guest lecture and community service program. This program took place in conjuction with the 'Academic Nexus Programme (ANP): Catalysing Research Collaboration through USUUiTM,' which was held from 4 to 10 September 2023 that targeted to fulfilled PI 084 through a number of international activities for the active status of MoU/ MOA.